A revised and extended systematic review and meta-analysis of the relationship between childhood adversity and adult psychiatric disorder. (December 2022) - McKay, Michael T.; Kilmartin, Leah; Meagher, Alexandra; Cannon, Mary; Healy, Colm; Clarke, Mary C.
Abstract: This study aimed to systematically review the evidence for an association between adversity experienced in childhood (≤ 17 years old), and the diagnosis of psychiatric disorder in adulthood. Electronic databases (Scopus, Medline (for Ovid), EMBASE, and PsychINFO) were searched for peer-reviewed, longitudinal cohort studies examining child or adolescent exposure to adversity, and adult-diagnosed depression, anxiety, psychotic disorder, eating disorders, substance abuse disorder, illness anxiety disorder, somatoform disorder, or personality disorder. A total of 39 manuscripts were retained. Results revealed a significant association between the following childhood exposures and adult mental disorder (1.24 ≤ Odds ratios ≤ 2.09): bullying (victimhood, and frequency); emotional abuse; neglect; physical abuse; parental loss; and general maltreatment (unspecified and/or multiple adversity exposure). There were opposing results for being a victim and perpetrator of bullying, and the result for sexual abuse was not statistically significant. There was some evidence of a dose-response relationship with those exposed to multiple forms of maltreatment having more two and a half times odds of developing a mental disorder (Odds ratio = 2.59). The result for sexual abuse is likely an artefact of the prospective assessment of this adversity. In summary, there was strong evidence of an association between childhood adversity and later mental illness, and this supports previously reported meta-analyses. The evidence suggests that childhood and adolescence is an important time for risk for later mental illness, and an important period in which to focus intervention strategies for those known to have been exposed to adversity, particularly multiple adversities.